Revisiting Full Reduplication in Indonesian, Javanese, and Sundanese Verbs: a Distributed Reduplication Approach - Agus Subiyanto (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
Indonesian, Javanese and Sundanese belong to the same language family, the Austronesian languages. The three languages have some similarities, one of which is the occurrence of reduplication. This paper aims to discuss full reduplication in the three languages, especially on the verbs. The objectives of this paper are to explain the semantic functions of full reduplication, and to present the process of deriving full reduplication in the three languages. In this case, the theory of distributed reduplication was applied in the analysis. The data used in the study were taken from books and research reports. In addition, I also employed a native speaker of  Sundanese to check the data on Sundanese. In this case, I used the interview method with an elicitation technique. The result of the analysis shows that Indonesian and Javanese have full reduplication with the notion of repetition, reciprocal, uncertainty of goal, and intensifier. Meanwhile, Sundanese, has full reduplication with the notion of intensifier and reciprocal. The process of full reduplication in the three language is different. In Indonesian, reduplicated forms with a reciprocal notion are composed of three morphemes, while in Javanese and Sundanese this type of reduplication is composed of two morphemes.Keywords: full reduplication, Indonesian, Javanese, Sundanese, distributed reduplication